2021
DOI: 10.1177/00048674211009619
|View full text |Cite
|
Sign up to set email alerts
|

Ageing with psychosis – Fifty and beyond

Abstract: Objective: While there is considerable current emphasis on youth and early psychosis, relatively little is known about the lives of people who live with psychotic disorders into middle age and beyond. We investigated social functioning, physical health status, substance use and psychiatric symptom profile in people with psychotic disorders aged between 50 and 65 years. Methods: Data were collected as part of the Survey of High Impact Psychosis, a population-based survey of Australians aged 18–65 years with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The older group contained more women, were more likely to have an affective component and more likely to be living alone. The authors concluded that the characteristics of people with psychosis change significantly as they progress into the middle age and beyond and emphasized that a better understanding of these differences is important in informing targeted treatment strategies for older people living with psychosis (Galletly et al, 2022). Symptomatic remission, psychosocial remission and functioning could be achievable goals for a considerable number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The older group contained more women, were more likely to have an affective component and more likely to be living alone. The authors concluded that the characteristics of people with psychosis change significantly as they progress into the middle age and beyond and emphasized that a better understanding of these differences is important in informing targeted treatment strategies for older people living with psychosis (Galletly et al, 2022). Symptomatic remission, psychosocial remission and functioning could be achievable goals for a considerable number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from the Survey of High Impact Psychosis, an Australian population survey of adults with psychotic disorders, Galletly et al [42] compared social functioning in the age group between 18 and 49 (n = 1478) with that in the 50 to 65 age group (n = 347). The older group, which contained a higher proportion of women, had a smaller social network, attributable perhaps to unemployment (no work colleagues), and high divorce rates.…”
Section: The Role Of Social Networkmentioning
confidence: 99%